Re-do Kasai procedure in a preterm infant - Hiromu Tanaka; Hideyuki Sasaki; Masatoshi Hashimoto; Masaki Nio (Elsevier, 2019)
We report the case of a 10-day old boy with biliary atresia (BA) who was delivered by caesarean section at 33 weeks 4 days of gestation (birth weight, 2135 g). At birth, his direct bilirubin level was high, and stools were light yellow. Abdominal ultrasonography showed no triangular cord sign, and duodenal fluid examination showed no bile. We performed a Kasai procedure (KP) 27 days after birth. His liver biopsy showed intrahepatic bile duct reduction. No bile excretion occurred postoperatively. We performed a redo KP 83 days after birth. Postoperative bile excretion was good, and his jaundice promptly resolved. The patient's liver biopsy showed bile duct development. Jaundice recurred at 8 months of age, and brain-dead-donor liver transplantation was required. The patient died of liver failure at 23 months of age.Surgery for BA during the neonatal period is usually effective, and the results of re-operation in cases with poor postoperative biliary excretion are poor. Here, we present a novel case that illustrates the progression and timing of the pathological hepatic changes in BA and consider the indications for and timing of re-operation in preterm infants. Keywords: Biliary atresia, Kasai procedure, Bile duct diseases, Premature, Reoperation